O imaginário na história de vida do professor de matemática - Wermuth, Silvia Betris Bender (2005)
incontestable, has become insufficient. It is the end of the absolut certainties. All these apprehensions stimulated me to perform this research, where I search the math teacher’s imaginary from his/her life stories with the intention to contribute in his/her search of the overcoming of always being right and the truth mighty demand. The miths that fulfill math with values and expectations that come from stories of the High school teacher will be considered and his/her imaginary to perform an approach to the analysis of the ways of cooperation or conflict in math teaching will be highlighted. Considering that every pedagogical act is a political act and that teaching demands understanding that education is a way of interference in the world, I have closen the qualitative research once I am concerned of going beyond the studied reality description, searching other ways to act and transform. The research trajectory will be presented in five sequential acts. Its organization happened in a discontinuous way tough. I start the trajectory by my life story as a math teacher. Then, I search, on the western history, for hints to understand the power that math still has on parents and students. After, I present the teenager student and the math teaching. The forth oral life story, memory and imaginary were the tools that helped me to comprehend the narratives that are described in the fifth act. There I see the imaginary of the high school teacher having as references the ideas of Maffesoli, Morin, Teixeira and Postic. In the last act, with the help of theoretical references, and contributors I face the image people have of the math teacher. I try to overcome the little miths that impregnate his/her practice and to forsee new possibilities to the math teaching.